COVID-19 hospital outbreaks: Protecting healthcare workers to protect frail patients. An Italian observational cohort study. (January 2021) - Vimercati, Luigi; De Maria, Luigi; Quarato, Marco; Caputi, Antonio; Stefanizzi, Pasquale; Gesualdo, Loreto; Migliore, Giovanni; Fucilli, Fulvio Italo Maria; Cavone, Domenica; Delfino, Maria Celeste; Sponselli, Stefania; Chironna, Maria; et al.
Highlights: This study included 3570 healthcare workers who underwent nasopharyngeal and oropharyngeal swabs. The workers were divided into two groups based on COVID-19 patient contact type. SARS-CoV-2 infection prevalence is 0.45% (25 workers of 5750 subjected to protocol). We found that 0.52% were positive in the low-risk group and 13.16% were positive in the high-risk group. Prevention procedures reduce the risk related to SARS-CoV-2 for healthcare workers. Abstract: Objectives: To determine the prevalence of SARS-CoV-2 infection among exposed healthcare workers (HCWs) after preventive protocol implementation. Methods: A total of 5750 HCWs were included in the study. Those in contact with COVID-19 patients were allocated into a high-risk or a low-risk group based on contact type (PPE- or non-PPE-protected); high-risk workers underwent nasopharyngeal swab tests, while among low-risk workers, swab tests were carried out only for symptomatic workers (active surveillance). The prevalence was determined by real-time reverse transcriptase–polymerase chain reaction on nasopharyngeal samples. Results: 3570 HCWs had contact with 1065 COVID-19 patients. Among them, 3494 were subjected to active surveillance (low-risk group); 2886 (82.60%) were subjected to a swab test; and 15 were positive (0.52%). Seventy-six HCWs (2.13% of exposed) were included in the high-risk group, and a swab test was mandatory for each participant. Overall, 66 (86.84% of high-risk) were negative, and 10 were positive (13.16%), resulting in a higher risk of infection than in the low-risk group [OR = 29.00; 95% CI:12.56-66.94; p < 0.0001]. Conclusion: To date, the SARS-CoV-2 infection prevalence is 0.70% among exposed HCWs and 0.435% among all HCWs working at the examined university hospital. The correct use of PPE and the early identification of symptomatic workers are essential factors to avoiding nosocomial clusters.